Performance of the automated multiplex PCR Unyvero implant and tissue infections system in the management of diabetic foot osteomyelitis. (November 2018) - Dunyach-Remy, Catherine; Carrere, Charlotte; Marchandin, Hélène; Schuldiner, Sophie; Guedj, Anne-Marie; Cellier, Nicolas; Cadière, Axelle; Lechiche, Catherine; Sotto, Albert; Lavigne, Jean-Philippe
Aim: We evaluated the performance of Unyvero implant and tissue infections system (ITI) application (Curetis) to diagnose Diabetic Foot Osteomyelitis (DFOM).Patients & methods: The study was conducted in the Diabetic Foot reference center of Nîmes University Hospital (France) from 1 December 2016 to 31 May 2017. We compared the Unyvero ITI PCR to conventional culture and alternative molecular approaches.Results: A total of 79 patients with DFOM were included: 177 microorganisms were isolated by culture, 146 detected by PCR, resulting in a concordance level of 66.7% (65.0–68.4). Discrepant results were obtained for 45 samples, with 59 microorganisms being detected by PCR only (18 samples) or by culture only (27 samples).Conclusion: Unyvero ITI PCR represents an interesting additional diagnosis solution to manage DFOM. Graphical abstract: